Utilization of nanomaterials in MRI contrast agents and their role in therapy guided by imaging - Wang, Wenjia; Shang, Shufan; Wang, Ye; Xu, Bing (Frontiers in Bioengineering and Biotechnology, 2024)
Magnetic Resonance Imaging (MRI) is a globally acknowledged diagnostic procedure particularly recognized for its superior soft tissue contrast, high-resolution imaging, and non-ionizing radiation properties, making it an indispensable tool in the medical field. However, to optimize MRI's sensitivity and specificity towards certain diseases, use of contrast agents becomes necessary. Recent developments focus on nanomaterial-based MRI contrast agents to improve diagnostic accuracy and image quality. This review highlights advancements in such agents, including metal oxide nanoparticles, carbon-based materials, gold nanoparticles, and quantum dots. It discusses their roles in MRI-guided therapies like targeted drug delivery, hyperthermia, radiation therapy, photodynamic therapy, immunity-boosting therapy, and gene therapy.Insights into the future potential of MRI contrast agents in imaging medicine are also provided.